SOSIALISASI TEKNOLOGI IOT (INTERNET OF THINGS) DAN LORA (LONG RANGE) PADA PEGAWAI INDUSTRI PT. WANTECH INDONESIA - Winjaya, Fathurrozi; Darmawan, Arief; Wibowo, Agustinus Prasetyo Edy; Puspitasari, Mariana Diah (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The Industrial Revolution 4.0 is symbolized by innovations such as the Internet of Things (IoT), which drive efforts to integrate disruptive technologies like IoT, big data, artificial intelligence, and cloud computing into government initiatives to promote smart cities and enhance societal well-being. Therefore, this socialization activity was carried out using a lecture method on IoT (Internet of Things) and LoRa (Long Range) technology for industrial employees at PT. Wantech Indonesia. This initiative aims to equip industrial employees with knowledge of technologies that align with modern developments. This activity was spearheaded by lecturers from PPI Madiun as part of a community service initiative focused on raising awareness about IoT and LoRa technology. The program has yielded positive results within the community and has expanded knowledge regarding emerging technologies. During its implementation, industrial employees, in particular, showed great enthusiasm for the activity. The post-test results indicated that the material was well understood and effectively conveyed.